Dynamic load test on progressive collapse resistance of fully assembled precast concrete frame structures. (1st July 2020) - Zhou, Yun; Hu, Xiang; Pei, Yilin; Hwang, Hyeon-Jong; Chen, Taiping; Yi, Weijian; Deng, Lu
Highlights: Comparison of progressive collapse performance between RC and PC moment sub-frames under dynamic loads. A fully assembled PC moment sub-frame used dowel bars and corbel in the beam-column connection. Unlike the RC frame, catenary action was not developed in the PC frame. The dynamic response of the both frames can be evaluated by nonlinear finite element analysis. Abstract: The progressive collapse of reinforced concrete (RC) and precast concrete (PC) structures is one of the most critical failure scenarios and is consequently of great concern to the structural engineering community. In this study, two half-scale RC and PC moment sub-structures were designed to evaluate the progressive collapse performance under a sudden mid-column loss scenario. In the PC specimen, the beam-column connection was fully assembled using the dowel bars embedded in a corbel, and steel angle cleats were applied to the connection between the upper surface of the beam-end and column to further transmit the flexural moment. The beam-column joint was strengthened by horizontal hoops and U-shaped bars. The dynamic responses such as the load-carrying capacity, beam deflection, lateral displacement, failure modes, crack distribution, and rebar strains were evaluated. The test results showed that the load-carrying capacity of the PC specimen was 76.9% of that of the RC specimen, while the ultimate deflection of the mid-column in the PC specimen was 106.1% of that of the RC specimen. Ultimately, shear failure occurred in the dowel bar connection of the PC specimen. On the other hand, ductile failure occurred by fracture of beam rebars in the RC specimen. Under dynamic loading, compressive arch action (CAA) was developed in the both specimens, but the effective catenary action (CTA) was developed in the RC specimen only. Finite element analysis was performed, and the analysis results agreed well with the test results. The dynamic test results and analysis results showed that the RC specimen exhibited better progressive collapse performance than the PC specimen.